THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FINANCIAL DISTRESS IN GENERAL INSURANCE COMPANIES IN INDONESIA - Setyaningrum, Novi Tri; Shalihah, Dian Karunia (Soedirman Accounting, Auditing and Public Sector Journal, 2024)
This study examines the influence of Good Corporate Governance (GCG), specifically the size of the board of commissioners, on financial distress in general insurance companies in Indonesia registered with the Financial Services Authority (OJK) in 2023. The study highlights the crucial role that insurance companies play in the country's financial and economic stability, while also acknowledging the challenges posed by financial distress, which is often caused by ineffective governance. The research aims to understand how board size affects financial outcomes. This study employs a quantitative method using secondary data from the annual financial reports of 62 general insurance companies. The results indicate that the size of the board of commissioners does not have a significant impact on financial distress, as measured by the Altman Z-Score. The regression analysis revealed a negative relationship between board size and financial distress. These findings suggest that while GCG practices are important for the overall governance of insurance companies, the size of the board may not be a determining factor in reducing financial distress.